Studies on the Absorption of Radiocalcium from Seawater in Three-line Grant (Parapristipoma trilineatum) in Relation to Dietary Calcium - Hossain, M Amzad (The Agriculturists, 2010)
A study was conducted to know the absorption of 45Ca from seawater in three-line grant in presence of dietary Ca. Juveniles of three-line grant were fed diets with calcium (Ca) supplement from Ca-lactate or without Ca supplement for 2 weeks, then exposed to seawater containing 45CaCl2. Overall 45Ca absorption from seawater was higher in this species. Absorption rate was rapid initially and become slow with the increase in exposure time. After 23 hours exposure, absorption of 45Ca was higher in fish fed a diet without Ca supplement compared those fed with Ca supplement. It was found that in threeline grant Ca absorption from seawater increased in cases where dietary Ca supplement was lacking. Therefore, dietary Ca supplementation may be dispensable for this species.